Analysing critical success factor of smart contract in construction industry with DANP approach - Rasti, Hooman; Feili, Ardalan; Sorooshian, Shahryar (Frontiers in Built Environment, 2024)
In all country construction projects include an enormous number of financial transactions and it’s necessary that the contracts between stakeholders should be more advanced in technology. The advance of Blockchain technology has been incontrovertible in recent years and this allowed the contracts to be programmed on Blockchain as smart contracts. The main goal of this paper is to identify and prioritize critical success factors of Smart Contracts in the construction industry. For identifying factors, we used library study and for prioritizing them, field study. To collect data, we designed a DANP questionnaire, from a panel senior managers and engineering experts. The results show that technology maturity is the most important factor in Smart Contract success; security of contracts, support from the engineering community, stakeholders’ consideration, and competition in the building industry were other important factors which took their next levels.